2006
DOI: 10.1111/j.1365-2435.2006.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf endophytes affect mycorrhizal status and growth of co‐infected and neighbouring plants

Abstract: Summary 1.Fungal leaf endophytes and arbuscular mycorrhizal (AM) fungi are common constituents of natural grasslands. The simultaneous presence of these two grass plant symbionts is highly probable. 2. We describe the results of a glasshouse experiment investigating the outcome of dual infection of a cool-season grass species, Lolium multiflorum , by the fungal endophyte Neotyphodium occultans and three species of Glomus AM fungi. 3. Mycorrhizal colonization was investigated on monocultures of plants with or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 52 publications
5
101
2
Order By: Relevance
“…For instance, a more complete occupation of aboveground resource space by vegetative tillers may enhance the competitive ability of endophyte-infected plants (Clay and Schardl 2002;Omacini et al 2006; but see Faeth et al 2004). Nevertheless, we found that endophyte infection led to higher biomass accrual of L. multiXorum populations in a low recruitment year (2003), but not in a high recruitment year (2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, a more complete occupation of aboveground resource space by vegetative tillers may enhance the competitive ability of endophyte-infected plants (Clay and Schardl 2002;Omacini et al 2006; but see Faeth et al 2004). Nevertheless, we found that endophyte infection led to higher biomass accrual of L. multiXorum populations in a low recruitment year (2003), but not in a high recruitment year (2004).…”
Section: Discussionmentioning
confidence: 98%
“…Endophyte incidence in Italian ryegrass populations has been reported to rise from 30% in recently abandoned Welds to nearly 90% after several years of succession (VilaAiub et al 2005). When grown in pots, infected plants sometimes perform better than endophyte-free conspeciWcs (Vila-Aiub et al 2005;Omacini et al 2006), but no comparable data exist for Weld populations.…”
Section: Study Speciesmentioning
confidence: 96%
“…Our use of semi-selective medium may also have allowed us to recover B. cinerea in the presence of more competitive fungi. Some fungal endophytes are known to produce secondary metabolites that are beneficial to the host in that they protect the plant against root-invading nematodes (Hallmann and Sikora, 1996); others benefit plant growth or alter nutrient cycling (Lemons et al, 2005;Omacini et al, 2006), and there are widespread reports of endophytes altering insect-plant interactions (Jallow et al, 2008). Although D'Amico et al (2008) showed that cultures of most of the fungi they recovered were pathogenic when inoculated to axenicallygrown plants in tissue culture jars, this is not very informative about the ecological function of the fungi in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Many fungi are involved, which may exist as saprotrophs (eg Acremonium strictum (Jallow et al 2008)), be vertically transmitted via seed (eg the Neotyphodium endophytes of grasses (Lemons et al 2005)), or reproduce via production of propagules at distinct phases of the host life-cycle (eg choke disease, (Tintjer et al, 2008)). Endophytes have been shown to affect insect damage both directly and indirectly (Hartley and Gange, 2009), to alter suscep-and viruses, and to alter mycorrhizal status (Omacini et al, 2006). By contrast, Botrytis cinerea (teleomorph Botryotinia fuckeliana) is regarded as a model necrotrophic organism (Williamson et al, 2007), and causes considerable problems in many sectors of temperate horticulture (Elad et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Soil samples were used in a control experiment for seedling emergence. Before the experiment, soil was sterilized in an oven for 72 h at 80°C to kill any plant seeds [40].…”
Section: Factors Measurement Of Dacrydium Pierreimentioning
confidence: 99%